Behaviour of Self-Consolidating Concrete Two Way Slabs Under Uniform Loading (Iraqi Journal of Civil Engineering, 2012)
An experimental investigation was conducted to study the strength, behaviour and deflection characteristics of two way slabs made with both self-consolidating concrete (SCC) and conventional concrete (CC). Six concrete slabs were tested to failure under simply supported uniform by distributed loading conditions. The variables were concrete type and macro synthetic fibres ratio (0%, 0.07% and 0.14%). The performance was evaluated based on crack pattern, ultimate load, load-deflection response and failure mode. The results showed that the ultimate strength of SCC slabs was larger than that of their CC counterparts. The results also showed an improvement of the behaviour and strength of slabs by adding the synthetic fibres.